Middle Pleistocene Pongo from Ganxian Cave in southern China with implications for understanding dental size evolution in orangutans. Issue 178 (May 2023) - Liang, Hua; Harrison, Terry; Shao, Qingfeng; Bahain, Jean-Jacques; Zhao, Jianxin; Bae, Christopher J.; Liao, Wei; Wang, Wei
Abstract: The Pongo fossil record of China extends from the Early Pleistocene to the Late Pleistocene, but to date, no late Middle Pleistocene samples of Pongo with precise absolute dating have been identified in southern China. Here, we report the recovery of 106 fossil teeth of Pongo from Ganxian Cave in the Bubing Basin, Guangxi, southern China. We dated the speleothems using Uranium-series and dated the two rhinoceros teeth using coupled electron spin resonance/Uranium-series dating methods to between 168.9 ± 2.4 ka and 362 ± 78 ka, respectively. These dates are consistent with the biostratigraphic and magnetostratigraphic age estimates. We further describe the fossil teeth from Ganxian Cave and compare them metrically to samples of fossil Pongo (i.e., Pongo weidenreichi, Pongo duboisi, Pongo palaeosumatrensis, Pongo javensis, and Pongo sp.) from the Early, Middle, and Late Pleistocene and to extant Pongo (i.e., Pongo pygmaeus and Pongo abelii ) from Southeast Asia. Based on overall dental size, a high frequency of lingual cingulum remnants on the upper molars, and a low frequency of moderate to heavy wrinkling on the molars, we attribute the Ganxian fossils to P. weidenreichi . Compared with Pongo fossils from other mainland Southeast Asia sites, those from Ganxian confirm that dental size reduction of Pongo occurred principally during the Early and Middle Pleistocene. From the Middle to Late Pleistocene, all teeth except the P 3 show little change in occlusal area, indicating that the size of these teeth remained relatively stable over time. The evolutionary trajectory of the Pongo dentition through time may be more complex than previously thought. More orangutan fossils with precise dating constraints are the keys to solving this issue.